2006
DOI: 10.1182/blood-2005-09-3596
|View full text |Cite
|
Sign up to set email alerts
|

Clarifying the role of Stat5 in lymphoid development and Abelson-induced transformation

Abstract: IntroductionStat molecules are part of a highly conserved signaling pathway involved in cell-fate decisions like differentiation, proliferation, and apoptosis. [1][2][3] The cytokines interleukin-2, -4, and -7 (IL-2, IL-4, IL-7) regulate important aspects of lymphoid development and are strong activators of the transcription factors Stat5a and Stat5b. 4 The importance of Stat5a/b for lymphoid cells is also underlined by the fact that constitutively activated Stat5a/b are found in several forms of lymphoid leuk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
234
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 196 publications
(249 citation statements)
references
References 58 publications
11
234
1
Order By: Relevance
“…Furthermore, STAT5, which regulates CYCLIN D1 and BCL-xL, is activated by BCR-ABL independent of Jak family proteins (Xie et al, 2001). STAT5a/b-deficient fetal liver hematopoietic progenitors fail to generate leukemia in recipient mice after retroviral transduction with BCR-ABL (Hoelbl et al, 2006). Among these BCR-ABL-related signaling molecules, we previously found that STAP-2 binds to and regulates c-CBL and STAT5 (Sekine et al, , 2009b.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, STAT5, which regulates CYCLIN D1 and BCL-xL, is activated by BCR-ABL independent of Jak family proteins (Xie et al, 2001). STAT5a/b-deficient fetal liver hematopoietic progenitors fail to generate leukemia in recipient mice after retroviral transduction with BCR-ABL (Hoelbl et al, 2006). Among these BCR-ABL-related signaling molecules, we previously found that STAP-2 binds to and regulates c-CBL and STAT5 (Sekine et al, , 2009b.…”
Section: Discussionmentioning
confidence: 99%
“…Stat5 dominant negative mutants block growth-factor independence and leukemogenic potential of Bcr-Abltransformed myeloid cells (Nieborowska-Skorska et al, 1999). Stat5ab À/À mice die perinatally and liver hematopoietic progenitors from these mice transfected with Bcr-Abl fail to generate leukemia in recipient mice (Hoelbl et al, 2006). RNAi-mediated reduction in Stat5 inhibits Bcr-Abl-dependent proliferation, but not cytokine-dependent proliferation and reduces myeloid colony formation in CML patient samples (Scherr et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…However, differentiation towards mature B cells seems to be unaffected. 5,6 STAT5 is also involved in the regulation of IL-7-dependent germline transcription, histone acetylation and DNA recombination of distal VH gene segments, which are the hallmark of B lymphocyte development. 7 Accordingly, a constitutively active form of STAT5B in IL-7R À / À mice, is sufficient to restore B-cell development.…”
Section: Introductionmentioning
confidence: 99%